The science of organizational design: Fit between structure and coordination - Richard M. Burton; Børge Obel (Journal of Organization Design, 2018)
Organization design is a major factor determining an organization's performance and how the people work together in these organizations. In the paper, we argue that designing organizations should be scientific-based and forward-looking. This raises challenges in designing organizations in contexts and situations that are new and have not been seen before. Experimentation of what is and what might be is the basis for exploring and examining what makes a good science for organizational design. Experimentation permits us to examine what might be for organization designs, which are not well understood or may not exist yet. Collaborative communities, new ventures, agile organizations, and temporary organizations are examples; experimentation permits us explore and examine what is and what might be and to examine the organizational design problem and perform experiments to understand the relationship between structure and coordination mechanisms of information, communications, decisions, trust, and incentives-the basis for the multi-contingency theory of organizational design.An organizational design must specify the fit between the structure of division of tasks in the organization with its coordination, or how to make these tasks work in concert. These tasks can be interdependent and uncertain. To design good organizations, we need empirical evidence about what is and exploration about what might be; we need a good theoretical basis for being able to generalize our knowledge. To illustrate our point, we examine two experiments on the classic M-form hypothesis-a computer simulation that examines coordination, organization structure, and interdependency and a laboratory experiment that examines the effect of incentives on opportunism and performance. Together, we find that the M-form is a robust organizational design, but with contingent conditions.Finally, we discuss how observation and experimentation together is the foundation for the development of scientific-based theory of organizational design.
Keywords: 650; Organisationsstruktur; Lernende Organisation; Experiment; Organisationstheorie